LITERASI SAINS DAN PENDIDIKAN KARAKTER DI ERA GLOBALISASI - Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
The era of globalization has had quite a broad impact on various aspects of life, especially in the administration of education, where quality human resources are an important factor in development in the current era of globalization. The method in this study is a literature review that discusses the importance of scientific literacy and character education in the era of globalization. So that in order to be able to overcome various problems that occur both political, economic and social, cultural as well as problems of moral and intellectual decadence, especially among students, it is necessary to strengthen the character of human resources and strong student scientific literacy based on the character of the Indonesian nation through various types of education. (formal, informal and non-formal) as well as at various levels of education (starting from primary, secondary and tertiary education).